The Lexicographic Features Of Artistic Phraseological Units - Mirsagatova Pokiza Avazbek kizi (Zien Journals, 2024)
The article is devoted to the current problem of lexicographic features of artistic phraseological units. The article shows the lexical-grammatical, structural diversity of writers' phraseology in the context of artistic phraseological units, the dependence of the choice of phraseological units of different expressivestylistic coloring, their functions and ability to vary from certain authorial settings
Keywords: artistic phraseological units; phraseological stylistics; functions of phraseological units